A single-phase ternary iron-based sulfide selenide composite material and its preparation method and application

Through the chelation of sodium alginate and iron ions and in situ crosslinking, combined with a one-step sulfur-selenization process, a single-phase ternary iron-based sulfur-selenide composite material was prepared, which solved the low conductivity and negative electrode material of sodium ion battery The problem of large volume changes has achieved high conductivity and structural stability, and improved the performance of the battery.

CN118811779BActive Publication Date: 2025-02-18LUOYANG INST OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411303231.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-02-18
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The low conductivity and large volume changes of the negative electrode material in sodium ion batteries lead to poor cycle stability and rate performance, and there are few researches on single-phase ternary materials, making synthesis difficult.

Method used

By using the structural characteristics of sodium alginate for chelation and in-situ crosslinking with iron ions, combined with one-step sulfur-selenization process and precise proportional regulation of sulfur and selenium sources, a single-phase ternary iron-based sulfur-selenide composite material was prepared. .

Benefits of technology

The high conductivity and structural stability of the material are achieved, the specific capacity, cycle stability and rate performance of sodium ion batteries are improved, and the cycle life of sodium storage is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118811779B_ABST
    Figure CN118811779B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of sodium ion battery electrode materials, specifically a single-phase ternary iron-based sulfide selenide composite material and its preparation method and application, wherein the preparation method is to use sodium alginate with abundant reserves as a precursor; utilize the abundant carboxyl and hydroxyl groups in the structure to crosslink the chelation between iron ions in one step to form a gel of sodium alginate wrapped metal; after the gel is refrigerated, it is simultaneously sulfide-selenized with sulfur and selenium sources by vapor deposition in an inert atmosphere, and the corresponding single-phase ternary iron-based sulfide selenide composite material can be obtained after cooling to room temperature. The present invention has the characteristics of improving material structure and performance, improving the electrochemical properties of such negative electrode materials, including material conductivity, structural stability, specific capacity, cycle stability and rate performance of sodium ion batteries, and significantly improving the cycle performance and rate performance of sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion battery electrode materials, and in particular to a single-phase ternary iron-based selenide sulfide composite material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries (SIBs) have a similar working mechanism to lithium-ion batteries, and are relatively more abundant in reserves, have better low-temperature performance, and are safer, making them the best alternative in some areas. Although sodium-ion batteries have their unique advantages, sodium has a larger ionic radius than lithium-ion batteries. This size difference leads to slower ion diffusion kinetics and more obvious volume expansion during repeated charge and discharge, which in turn becomes a serious obstacle to achieving long-cycle stability and high-rate sodium-ion batteries. As an important component of sodium-ion batteries, the performance of negative electrode materials also indirectly determines the performance of the entire battery. Currently, conversion materials in negative electrode materials have been proven to have high theoretical capacities, such as metal oxides, metal phosphides, and metal chalcogenides.

[0003] Among them, transition metal chalcogenides (TMCs), including MoS2, FeS2, CoS2, NiS2, MoSe2, FeSe2, etc., have been used as high-capacity sodium-ion battery anode materials. Their advantages are high theoretical capacity, good electrochemical properties and structural versatility. However, low conductivity and large volume changes hinder the practical application of such anode materials. Therefore, strategies such as nanostructure engineering, carbon material modification, and ion doping have been proposed to overcome the above problems. At present, most of the reported work is mainly based on binary materials, and single-phase ternary materials are less studied. Single-phase ternary materials contain two different anions, which will produce many atomic-level interfaces. The coexisting two anions can further adjust the electronic structure of the material and affect the physical and chemical properties. The difference in redox potential prompts the anions to participate in the electrochemical reaction asynchronously, showing excellent electrochemical properties in the sodium-ion battery system. The reported single-phase ternary materials are mainly concentrated in metal phosphosulfide (MPS) or metal phosphoselenide (MPSe), while metal sulfide selenide (MSSe) is relatively rare, and the synthesis of single-phase ternary materials is relatively difficult.

[0004] Chinese patent CN117334907A discloses a method for preparing a three-dimensional porous carbon-based selenide / iron sulfide composite material. The patent forms gel particles through a sodium alginate solution containing graphene oxide and metal iron ions, and then obtains a carbon-based selenide / iron sulfide composite material by first sulfidation and then selenization. The composite material includes porous carbon nanobelts, iron selenide and iron sulfide. The added graphene oxide increases the material cost; the step-by-step sulfidation and selenization process is complicated and the uncontrollability increases; the electrochemical activity of the prepared selenide / iron sulfide composite material is lower than that of the single-phase ternary material.

[0005] Based on this, the present invention aims to construct a single-phase ternary material through low-cost raw materials, a simple one-step sulfur-selenization process and precise ratio control of sulfur and selenium sources. Summary of the invention

[0006] In order to solve the above problems, the purpose of the present invention is to provide a single-phase ternary iron-based sulfide selenide composite material and its preparation method and application, which makes full use of the strong chelation between the abundant carboxyl and hydroxyl groups in the structure of sodium alginate (SA) and iron ions and the in-situ cross-linking reaction of sodium alginate, and then prepares a single-phase ternary iron-based sulfide selenide composite material by adjusting the molar ratio of sulfur and selenium sources. The composite material not only contains abundant FeS 2-x Se x Active sites can effectively reduce the internal stress of the material; at the same time, the in-situ cross-linking of sodium alginate derived carbon network can significantly improve the conductivity of the material and accelerate electron transport.

[0007] The present invention provides a method for preparing a single-phase ternary iron-based sulfide-selenide composite material, which specifically comprises the following steps:

[0008] (1) Place a certain amount of sodium alginate in water, then heat and stir it in a water bath until it is completely dissolved. After stirring, cool it to room temperature and let it stand to expel bubbles to form a gel solution, which is solution A. Dissolve Fe(NO3)3•9H2O in water to prepare solution B.

[0009] (2) Add solution A dropwise into solution B under slow stirring, and a ball-dropping phenomenon occurs. After all solution A is added into solution B, stirring is stopped to obtain a mixture C. The mixture C is placed in a constant temperature water bath for static adsorption. After the adsorption is completed, the formed spherical substance is washed with deionized water for multiple times. After the washing is completed, the obtained spherical substance is freeze-dried, and the product obtained after the drying is SA-Fe.

[0010] (3) The SA-Fe powder obtained in step (2) is placed in a porcelain boat A, and the sulfur powder and selenium powder are placed in a porcelain boat B. The porcelain boat A is then placed downstream of a tubular furnace, and the porcelain boat B is placed upstream of the tubular furnace. The temperature is then raised to a certain temperature under an inert atmosphere, and then kept constant at this temperature for a period of time. After the constant temperature ends, it is naturally cooled to room temperature to obtain a single-phase ternary iron-based sulfur-selenide composite material, which is recorded as SA-Fe-S / Se.

[0011] Furthermore, in step (1), the mass concentration of sodium alginate in solution A is 0.01-0.05 g / mL, and the water used is deionized water; the heating and stirring temperature is 60-90° C., and the stirring time is 0.5-2 hours.

[0012] Furthermore, in step (1), the concentration of Fe(NO3)3•9H2O in solution B is 0.1-0.3 mol / L;

[0013] Furthermore, in step (2), the temperature of the constant temperature water bath is 25-50° C., the static adsorption time is 12-36 hours, the volume of deionized water used for each washing is 800-1500 mL, and the freeze-drying time is 24-72 hours.

[0014] Furthermore, in step (3), the molar ratio of sulfur powder to selenium powder is 5:1-2:4; the inert atmosphere is N2 atmosphere, the heating rate is 1-4°C / min, the temperature is raised to 400-700°C, and the constant temperature time is 3-8 hours.

[0015] Furthermore, in step (3), sulfur powder and selenium powder are placed in porcelain boat B, specifically, sulfur powder is placed downstream of porcelain boat B and selenium powder is placed upstream of porcelain boat B.

[0016] The present invention also provides a single-phase ternary iron-based sulfide selenide composite material obtained according to the above preparation method and the use of the single-phase ternary iron-based sulfide selenide composite material as a negative electrode material for a sodium ion battery.

[0017] Furthermore, the single-phase ternary iron-based sulfide selenide composite material has a mutually cross-linked porous carbon network structure, and the single-phase ternary iron-based sulfide selenide particles are wrapped in the porous carbon network structure.

[0018] In the preparation method of the present invention, the chelation between iron ions is cross-linked in one step by utilizing the abundant carboxyl and hydroxyl groups in the structure of sodium alginate to form a sodium alginate-wrapped metal (SA-Fe) gel; after the gel is freeze-dried, it is simultaneously sulfur-selenized with sulfur and selenium sources by vapor deposition in an inert atmosphere, and the corresponding single-phase ternary SA-Fe-S / Se product can be obtained after cooling to room temperature. The preparation method utilizes the unique structural advantages of sodium alginate and its chelation effect on metals, and obtains the target product through only two steps of chelation-crosslinking and simultaneous sulfur-selenization. The production process is simple and easy to implement, the cycle is short, and the stability is good.

[0019] The present invention uses sodium alginate, which is widely available and inexpensive, as a carbon-based precursor, and prepares a sodium ion battery negative electrode material in which a single-phase ternary iron-based sulfide selenide nanoparticle is uniformly wrapped in a carbon matrix through a simple chelation-crosslinking and one-step sulfide selenization strategy. The single-phase ternary iron-based sulfide selenide composite material has a mutually cross-linked carbon network structure, and the active nanoparticles are uniformly wrapped in the network. The wrapped small-sized nanoparticles can effectively enhance the conductivity of the material, promote the rapid transmission of electrons during the cycle, and thus improve the material rate performance and cycle stability; the carbon-based wrapping further enhances the conductivity of the material and constrains the volume expansion caused by the material, slows down the capacity decay, and improves the long cycle life of sodium storage; in addition, the single-phase ternary SA-Fe-S / Se product formed can further buffer the internal stress during the sodium insertion and extraction process. The developed conductive network constructed by the in-situ derived carbon base accelerates the electron transmission rate and improves the material rate performance.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The preparation method proposed in the present invention utilizes the structural advantages of the sodium alginate precursor and obtains the target product through only two steps of chelation-crosslinking and sulfur / selenization. The obtained material has high yield, good stability and strong repeatability, which provides an option for exploring large-scale synthesis of high-rate sodium ion battery negative electrode materials with excellent performance;

[0022] (2) The process adopted by the present invention is simple and easy to implement, has low requirements on equipment, and has a short production cycle. In addition, the precursor sodium alginate has a wide source, low cost, and great application potential;

[0023] (3) The present invention can realize the preparation of single-phase ternary iron-based sulfide selenide by simple one-step sulfide selenization and precise ratio control of sulfur and selenium sources, rather than the conventional two-phase mixture of iron sulfide and iron selenide. The single-phase ternary material obtained by simultaneous sulfide selenization has special electronic structure characteristics and atomic-level interface effects, as well as higher electrochemical activity compared to the two-phase mixture obtained in steps; the single-phase ternary material FeS 2-x Se x The two anions S and Se are evenly mixed, resulting in many atomic-level interfaces. At the same time, the coexistence of S and Se can further regulate the electronic structure of the Fe atom in the metal center, affect its physical and chemical properties, and enhance the electrochemical reaction kinetics. In addition, the charge distribution between the metal Fe atom and the Fe-S / Fe-Se bond in the single-phase ternary material is different, resulting in the aggregation and diffusion of charges, thereby enhancing the interaction between the bond atoms and improving the structural stability;

[0024] (4) The single-phase ternary iron-based sulfide-selenide composite material obtained by the preparation method of the present invention improves the conductivity of the material, accelerates the electron migration speed and shortens the electron diffusion distance, thereby effectively improving the electrochemical performance of the material;

[0025] (5) When the single-phase ternary iron-based sulfide-selenide composite material obtained by the preparation method of the present invention is used as a negative electrode material for a sodium ion battery, it is tested at a current density of 1A / g. The initial charge and discharge specific capacities can be as high as 676.92mAh / g and 847.38mAh / g, respectively. After 676 cycles, the charge and discharge specific capacities can still be maintained at 525.05mAh / g and 616.46mAh / g, showing excellent long-cycle performance; even after 5231 cycles at a high current density of 3 A / g, the discharge specific capacity can still reach 225mAh / g, showing good long-life performance; in the rate performance test at different current densities, the prepared single-phase ternary iron-based sulfide-selenide composite material still shows a good capacity retention rate. The above test results show that the single-phase ternary iron-based sulfide-selenide composite material prepared by this simple process is not only endowed with high sodium storage performance, but also has excellent rate characteristics, and is a potential application material for high energy density and high power density sodium ion batteries;

[0026] (6) The present invention utilizes chelation-crosslinking and simultaneous sulfur / selenization strategies to construct a composite material of sodium alginate in situ derived carbon coated single-phase ternary iron-based sulfur-selenide active sites, thereby further improving the material structure and performance, and enhancing the electrochemical properties of this type of negative electrode material, including material conductivity, structural stability, and the specific capacity, cycle stability and rate performance of sodium ion batteries, and has the characteristics of significantly improving the cycle performance and rate performance of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a SEM image of SA-Fe prepared in Example 1;

[0028] Figure 2 is a SEM image of SA-Fe-S / Se-5:1 prepared in Example 1;

[0029] Figure 3 The XRD patterns of SA-Fe-S / Se-5:1 prepared in Example 1, SA-Fe-S / Se-1:1 prepared in Example 2, SA-Fe-S prepared in Comparative Example 1, SA-Fe-Se prepared in Comparative Example 2, and SA-Fe-S / Se-1:5 prepared in Comparative Example 3 are shown;

[0030] Figure 4 is the distribution diagram of the content of each element of SA-Fe-S / Se-5:1 prepared in Example 1;

[0031] Figure 5AC impedance diagram of sodium ion batteries with SA-Fe-S / Se-5:1 prepared in Example 1, SA-Fe-S / Se-1:1 prepared in Example 2, SA-Fe-S prepared in Comparative Example 1, SA-Fe-Se prepared in Comparative Example 2, and SA-Fe-S / Se-1:5 prepared in Comparative Example 3 as negative electrodes after 10 cycles at a current density of 1 A / g;

[0032] Figure 6 Cyclic performance curves of sodium ion batteries using SA-Fe-S / Se-5:1 prepared in Example 1, SA-Fe-S / Se-1:1 prepared in Example 2, SA-Fe-S prepared in Comparative Example 1, SA-Fe-Se prepared in Comparative Example 2, and SA-Fe-S / Se-1:5 prepared in Comparative Example 3 as negative electrodes at a current density of 1 A / g;

[0033] Figure 7 Cyclic performance curves of sodium ion batteries with SA-Fe-S / Se-5:1 prepared in Example 1, SA-Fe-S prepared in Comparative Example 1, and SA-Fe-Se prepared in Comparative Example 2 as negative electrodes at a current density of 3 A / g;

[0034] Figure 8 Rate performance curves of sodium ion batteries using SA-Fe-S / Se-5:1 prepared in Example 1, SA-Fe-S / Se-1:1 prepared in Example 2, SA-Fe-S prepared in Comparative Example 1, SA-Fe-Se prepared in Comparative Example 2, and SA-Fe-S / Se-1:5 prepared in Comparative Example 3 as negative electrodes;

[0035] Fig. 9 This is the cycle performance curve of a sodium ion battery using the SA-Fe-S-Se material prepared in Comparative Example 4 as the negative electrode at a current density of 1 A / g. DETAILED DESCRIPTION

[0036] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings. The following embodiments are implemented based on the technology of the present invention, and detailed implementation methods and operating steps are given, but the protection scope of the present invention is not limited to the following embodiments.

[0037] Embodiment 1:

[0038] (1) 3 g of sodium alginate was placed in 100 mL of deionized water, and then placed in a water bath at 80 °C and stirred for 1 hour to completely dissolve the sodium alginate powder. After stirring, the mixture was cooled to room temperature and allowed to stand to release bubbles to form a gel-like solution, which was Solution A. 28.76 mmol of Fe(NO3)3•9H2O was then dissolved in 200 mL of deionized water to prepare Solution B.

[0039] (2) Add solution A dropwise to solution B with a syringe under slow stirring, and a ball-dropping phenomenon occurs; after all solution A is added to solution B, stirring is stopped to obtain a mixture C, and the mixture C is placed in a constant temperature water bath at 30°C for adsorption for 24 hours; after the adsorption is completed, the formed spherical substance is washed three times with deionized water, and the amount of deionized water used each time is 1000 mL. The purpose of washing is to remove the physically adsorbed metal ions; after the washing is completed, the obtained spherical substance is freeze-dried for 48 hours, and the product obtained after the drying is SA-Fe;

[0040] (3) 600 mg of the SA-Fe powder prepared in step (2) was placed in a porcelain boat A, and 1 g of sulfur powder and 493.5 mg of selenium powder (i.e., the molar ratio of the sulfur powder to the selenium powder was 5:1) were placed in a porcelain boat B, with the sulfur powder being located downstream of the porcelain boat B and the selenium powder being located upstream of the porcelain boat B; then, the porcelain boat B was placed upstream of a tube furnace and the porcelain boat A was placed downstream of the tube furnace, and the temperature was increased to 450°C at a heating rate of 2°C / min under a N2 atmosphere, and the temperature was maintained constant for 6 hours. After the constant temperature was reached, the powder in the porcelain boat A was collected after the tube furnace was naturally cooled to room temperature. The powder was a single-phase ternary iron-based sulfur-selenide composite material, recorded as SA-Fe-S / Se-5:1.

[0041] Embodiment 2:

[0042] (1) 3 g of sodium alginate was placed in 100 mL of deionized water, and then placed in a water bath at 80 °C and stirred for 1 hour to completely dissolve the sodium alginate powder. After stirring, the solution was cooled to room temperature and the bubbles were discharged to form a gel solution, which was Solution A. Then, 28.76 mmol of Fe(NO3)3•9H2O was dissolved in 200 mL of deionized water to prepare Solution B.

[0043] (2) Add solution A dropwise to solution B with a syringe under slow stirring, and a ball-dropping phenomenon occurs; after all solution A is added to solution B, stirring is stopped to obtain a mixture C, and the mixture C is placed in a constant temperature water bath at 30°C for adsorption for 24 hours; after the adsorption is completed, the formed spherical substance is washed three times with deionized water, and the amount of deionized water used each time is 1000 mL. The purpose of washing is to remove the physically adsorbed metal ions; after the washing is completed, the obtained spherical substance is freeze-dried for 48 hours, and the product obtained after the drying is SA-Fe;

[0044] (3) 600 mg of the SA-Fe powder prepared in step (2) is placed in a porcelain boat A, and 600 mg of sulfur powder and 1.4805 g of selenium powder (i.e., the molar ratio of the sulfur powder to the selenium powder is 1:1) are placed in a porcelain boat B, with the sulfur powder being located downstream of the porcelain boat B and the selenium powder being located upstream of the porcelain boat B; then the porcelain boat B is placed upstream of a tube furnace and the porcelain boat A is placed downstream of the tube furnace, and the temperature is increased to 450°C at a heating rate of 2°C / min under a N2 atmosphere, and the temperature is maintained constant for 6 hours. After the constant temperature is reached, the powder in the porcelain boat A is collected after the tube furnace is naturally cooled to room temperature. The powder is a single-phase ternary iron-based sulfur-selenide composite material, recorded as SA-Fe-S / Se-1:1.

[0045] Embodiment 3:

[0046] (1) Place 1 g of sodium alginate in 100 mL of deionized water, then place it in a 60°C water bath and stir for 2 hours to completely dissolve the sodium alginate powder. After stirring, cool it to room temperature and let it stand to remove bubbles. The gel solution formed is Solution A. Then, dissolve 20 mmol of Fe(NO3)3•9H2O in 200 mL of deionized water to prepare Solution B.

[0047] (2) Add solution A dropwise to solution B with a syringe under slow stirring, and a ball-dropping phenomenon occurs; after all solution A is added to solution B, stirring is stopped to obtain a mixture C, and the mixture C is placed in a constant temperature water bath at 50°C for adsorption for 36 hours; after the adsorption is completed, the formed spherical substance is washed three times with deionized water, and the amount of deionized water used each time is 800 mL. The purpose of washing is to remove physically adsorbed metal ions; after the washing is completed, the obtained spherical substance is freeze-dried for 72 hours, and the product obtained after the drying is SA-Fe;

[0048] (3) 600 mg of the SA-Fe powder prepared in step (2) is placed in a porcelain boat A, and 400 mg of sulfur powder and 1.975 g of selenium powder (i.e., the molar ratio of the sulfur powder to the selenium powder is 2:4) are placed in a porcelain boat B, with the sulfur powder being located downstream of the porcelain boat B and the selenium powder being located upstream of the porcelain boat B; then the porcelain boat B is placed upstream of a tube furnace and the porcelain boat A is placed downstream of the tube furnace, and the temperature is increased to 400°C at a heating rate of 1°C / min under a N2 atmosphere, and the temperature is maintained constant for 8 hours. After the constant temperature is reached, the powder in the porcelain boat A is collected after the tube furnace is naturally cooled to room temperature. The powder is a single-phase ternary iron-based sulfur-selenide composite material, recorded as SA-Fe-S / Se-2:4.

[0049] Embodiment 4:

[0050] (1) Place 5 g of sodium alginate in 100 mL of deionized water, then place it in a 90°C water bath and stir for 0.5 hours to completely dissolve the sodium alginate powder. After stirring, cool it to room temperature and let it stand to remove bubbles. The gel solution formed is Solution A. Then, dissolve 60 mmol of Fe(NO3)3•9H2O in 200 mL of deionized water to prepare Solution B.

[0051] (2) Add solution A dropwise to solution B with a syringe under slow stirring, and a ball-dropping phenomenon occurs; after all solution A is added to solution B, stirring is stopped to obtain a mixture C, and the mixture C is placed in a constant temperature water bath at 25°C for 12 hours of static adsorption; after the adsorption is completed, the formed spherical substance is washed three times with deionized water, and the amount of deionized water used each time is 1500 mL. The purpose of washing is to remove physically adsorbed metal ions; after the washing is completed, the obtained spherical substance is freeze-dried for 24 hours, and the product obtained after the drying is SA-Fe;

[0052] (3) 600 mg of the SA-Fe powder prepared in step (2) is placed in a porcelain boat A, and 800 mg of sulfur powder and 987.5 mg of selenium powder (i.e., the molar ratio of the sulfur powder to the selenium powder is 2:4) are placed in a porcelain boat B, with the sulfur powder being located downstream of the porcelain boat B and the selenium powder being located upstream of the porcelain boat B; then the porcelain boat B is placed upstream of a tube furnace and the porcelain boat A is placed downstream of the tube furnace, and the temperature is increased to 700°C at a heating rate of 4°C / min under a N2 atmosphere, and the temperature is maintained constant for 3 hours. After the constant temperature is reached, the powder in the porcelain boat A is collected after the tube furnace is naturally cooled to room temperature. The powder is a single-phase ternary iron-based sulfur-selenide composite material, recorded as SA-Fe-S / Se-4:2.

[0053] Comparative Example 1:

[0054] This comparative example is a method for preparing an iron-based sulfide composite material, which is specifically as follows:

[0055] (1) 3 g of sodium alginate was placed in 100 mL of deionized water, and then placed in a water bath at 80 °C and stirred for 1 hour to completely dissolve the sodium alginate powder. After stirring, the solution was cooled to room temperature and the bubbles were discharged to form a gel solution, which was Solution A. Then, 28.76 mmol of Fe(NO3)3•9H2O was dissolved in 200 mL of deionized water to prepare Solution B.

[0056] (2) Add solution A dropwise to solution B with a syringe under slow stirring, and a ball-dropping phenomenon occurs; after all solution A is added to solution B, stirring is stopped to obtain a mixture C, and the mixture C is placed in a constant temperature water bath at 30°C for adsorption for 24 hours; after the adsorption is completed, the formed spherical substance is washed three times with deionized water, and the amount of deionized water used each time is 1000 mL. The purpose of washing is to remove the physically adsorbed metal ions; after the washing is completed, the obtained spherical substance is freeze-dried for 48 hours, and the product obtained after the drying is SA-Fe;

[0057] (3) 600 mg of the SA-Fe powder prepared in step (2) was placed in a porcelain boat A, and 1.2 g of sulfur powder was placed in a porcelain boat B. The porcelain boat B was then placed upstream of the tube furnace and the porcelain boat A was placed downstream of the tube furnace. The temperature was increased to 450°C at a heating rate of 2°C / min under a N2 atmosphere and kept constant for 6 hours. After the constant temperature was reached, the powder in the porcelain boat A was collected after the tube furnace was naturally cooled to room temperature. The powder was an iron-based sulfide composite material, which was recorded as SA-Fe-S.

[0058] Comparative Example 2:

[0059] This comparative example is a method for preparing an iron-based selenide composite material, which is specifically as follows:

[0060] (1) 3 g of sodium alginate was placed in 100 mL of deionized water, and then placed in a water bath at 80 °C and stirred for 1 hour to completely dissolve the sodium alginate powder. After stirring, the solution was cooled to room temperature and the bubbles were discharged to form a gel solution, which was Solution A. Then, 28.76 mmol of Fe(NO3)3•9H2O was dissolved in 200 mL of deionized water to prepare Solution B.

[0061] (2) Add solution A dropwise to solution B with a syringe under slow stirring, and a ball-dropping phenomenon occurs; after all solution A is added to solution B, stirring is stopped to obtain a mixture C, and the mixture C is placed in a constant temperature water bath at 30°C for adsorption for 24 hours; after the adsorption is completed, the formed spherical substance is washed three times with deionized water, and the amount of deionized water used each time is 1000 mL. The purpose of washing is to remove the physically adsorbed metal ions; after the washing is completed, the obtained spherical substance is freeze-dried for 48 hours, and the product obtained after the drying is SA-Fe;

[0062] (3) 600 mg of the SA-Fe powder prepared in step (2) was placed in a porcelain boat A, and 2.961 g of selenium powder was placed in a porcelain boat B. The porcelain boat B was then placed upstream of a tube furnace and the porcelain boat A was placed downstream of the tube furnace. The temperature was increased to 450°C at a heating rate of 2°C / min under a N2 atmosphere and kept constant for 6 hours. After the constant temperature was reached, the powder in the porcelain boat A was collected after the tube furnace was naturally cooled to room temperature. The powder was an iron-based selenide composite material, denoted as SA-Fe-Se.

[0063] Comparative Example 3:

[0064] This comparative example is a method for preparing an iron-based sulfide / selenide heterojunction composite material, which is specifically as follows:

[0065] (1) 3 g of sodium alginate was placed in 100 mL of deionized water, and then placed in a water bath at 80 °C and stirred for 1 hour to completely dissolve the sodium alginate powder. After stirring, the solution was cooled to room temperature and the bubbles were discharged to form a gel solution, which was Solution A. Then, 28.76 mmol of Fe(NO3)3•9H2O was dissolved in 200 mL of deionized water to prepare Solution B.

[0066] (2) Add solution A dropwise to solution B with a syringe under slow stirring, and a ball-dropping phenomenon occurs; after all solution A is added to solution B, stirring is stopped to obtain a mixture C, and the mixture C is placed in a constant temperature water bath at 30°C for 24 hours of static adsorption; after the adsorption is completed, the formed spherical substance is washed three times with deionized water, and the amount of deionized water used each time is 1000 mL. The purpose of washing is to remove physically adsorbed metal ions; after the washing is completed, the obtained spherical substance is freeze-dried for 48 hours, and the product obtained after the drying is SA-Fe;

[0067] (3) 600 mg of the SA-Fe powder prepared in step (2) was placed in a porcelain boat A, and 200 mg of sulfur powder and 2.4675 g of selenium powder (i.e., the molar ratio of the sulfur powder to the selenium powder was 1:5) were placed in a porcelain boat B, with the sulfur powder being located downstream of the porcelain boat B and the selenium powder being located upstream of the porcelain boat B; then, the porcelain boat B was placed upstream of a tube furnace and the porcelain boat A was placed downstream of the tube furnace, and the temperature was increased to 450°C at a heating rate of 2°C / min under a N2 atmosphere, and the temperature was maintained constant for 6 hours. After the constant temperature was reached, the powder in the porcelain boat A was collected after the tube furnace was naturally cooled to room temperature. The powder was an iron-based sulfide / selenide heterojunction composite material, recorded as SA-Fe-S / Se-1:5.

[0068] Comparative Example 4:

[0069] This comparative example is a method for preparing an iron-based sulfide / selenide heterojunction composite material, which is specifically as follows:

[0070] (1) 3 g of sodium alginate was placed in 100 mL of deionized water, and then placed in a water bath at 80 °C and stirred for 1 hour to completely dissolve the sodium alginate powder. After stirring, the solution was cooled to room temperature and the bubbles were discharged to form a gel solution, which was Solution A. Then, 28.76 mmol of Fe(NO3)3•9H2O was dissolved in 200 mL of deionized water to prepare Solution B.

[0071] (2) Add solution A dropwise to solution B with a syringe under slow stirring, and a ball-dropping phenomenon occurs; after all solution A is added to solution B, stirring is stopped to obtain a mixture C, and the mixture C is placed in a constant temperature water bath at 30°C for 24 hours of static adsorption; after the adsorption is completed, the formed spherical substance is washed three times with deionized water, and the amount of deionized water used each time is 1000 mL. The purpose of washing is to remove physically adsorbed metal ions; after the washing is completed, the obtained spherical substance is freeze-dried for 48 hours, and the product obtained after the drying is SA-Fe;

[0072] (3) 600 mg of the SA-Fe powder prepared in step (2) was placed in a porcelain boat A, and 1 g of sulfur powder was placed in a porcelain boat B. The porcelain boat B was then placed upstream of the tube furnace and the porcelain boat A was placed downstream of the tube furnace. The temperature was raised to 450°C at a heating rate of 2°C / min under a N2 atmosphere and kept constant for 6 hours. After the constant temperature was completed, the corresponding black sulfurized product powder in the porcelain boat A was collected after the tube furnace was naturally cooled to room temperature.

[0073] (4) The sulfide product obtained in step (3) is placed in a porcelain boat C, and 493.5 mg of selenium powder is placed in a porcelain boat D. Subsequently, the porcelain boat D is placed upstream of the tube furnace and the porcelain boat C is placed downstream of the tube furnace. The temperature is increased to 450°C at a heating rate of 2°C / min under a N2 atmosphere and kept constant for 6 hours. After the constant temperature is reached, the powder in the porcelain boat C is collected after the tube furnace is naturally cooled to room temperature. The powder is an iron-based sulfide / selenide heterojunction composite material, which is recorded as SA-Fe-S-Se.

[0074] SEM testing was performed using a ZEISS Gemini SEM 300 scanning electron microscope from Zeiss, Germany. A small amount of powdered sample was coated on a black conductive adhesive and then subjected to gold spraying. SEM can be used to characterize the surface microstructure and particle size of the sample.

[0075] Figure 1 The SEM image of SA-Fe prepared in Example 1 is shown in FIG. Figure 1 It can be seen that sodium alginate presents an interconnected porous network structure after adsorbing metal ions and in-situ self-crosslinking.

[0076] Figure 2This is the SEM image of SA-Fe-S / Se-5:1 prepared in Example 1. Figure 2 It can be seen from the figure that after the SA-Fe precursor is treated with sulfur / selenium, the network structure shrinks and partially adheres due to the loss of some functional groups and the reorganization of carbon, but the porous network structure can still be well maintained. Figure 2 No nanoparticles with mesh-like surface agglomeration were found, indicating that the formed single-phase ternary iron-based sulfide selenide particles were well wrapped in the carbon network. This coating not only helps to improve the conductivity of the material, but also has a restraining effect to effectively alleviate the volume change of active particles during the charge and discharge process and improve the sodium storage capacity. On the other hand, the constructed porous conductive carbon network is conducive to the rapid transmission of electrons and enhances the material rate performance.

[0077] XRD test was performed using a D / max-γβ X-ray diffractometer produced by Rigaku Corporation to analyze the composition and structure of the samples. Figure 3 , XRD analysis shows that the SA-Fe-S product prepared in Comparative Example 1 is mainly composed of FeS2 species, and the intensity of each diffraction peak is relatively weak, indicating that when only a single sulfur source exists during the preparation process, the product only has FeS2 with poor crystallinity. However, when a small amount of selenium source is added, a strong derivative peak appears in the XRD curve of SA-Fe-S / Se-5:1 prepared in Example 1, and the peak position is shifted to a smaller angle as a whole compared to the standard FeS2 (PDF No.42-1340). At the same time, the XRD curve of SA-Fe-S / Se-1:1 prepared in Example 2 also shows a similar situation, and the offset angle is larger. The increase in the intensity of the derivative peak indicates that the introduction of selenium induces a significant enhancement in the crystallinity of the product. The shift in the position of the derivative peak is due to the fact that the introduced large atomic radius Se gradually enters the lattice of FeS2 and partially replaces the S site with a small atomic radius, causing the lattice to expand, but the coexistence of the two phases of FeS2 / FeSe2 is not formed, indicating that the product formed is FeS 2-x Se x A single-phase ternary composite material mainly composed of FeS and a small amount of FeSe2 species is obtained. When the amount of Se source is continued to be increased to a certain content, the XRD curve of SA-Fe-S / Se-1:5 prepared in Comparative Example 3 shows that the product is mainly composed of FeS and a small amount of FeSe2 species. The generation of FeSe2 species is mainly due to the fact that the material is relatively in a Se-rich atmosphere, and the formed iron-based sulfide is more easily completely replaced to form iron-based selenide, and the residual iron-based sulfide exists in the form of FeS. When only one selenium source is used, the SA-Fe-Se product prepared in Comparative Example 2 is mainly composed of FeSe2 species and contains a small amount of Fe2O3 species. The existence of iron-based oxides is mainly due to the fact that S with a stronger electronegativity is more likely to form sulfides with metal ion structures, while Se with a weaker electronegativity is relatively difficult, so the product contains not only selenides, but also a small amount of incompletely selenized oxides.

[0078] Figure 4 This is the element content distribution diagram of the SA-Fe-S / Se-5:1 composite material prepared in Example 1 obtained by scanning the corresponding surface during SEM testing. Figure 4 It can be seen that the mass percentages of C, S, Se, and Fe in the material are 66.1%, 6.8%, 0.7%, and 7.5%, respectively. The higher content of carbon comes from sodium alginate. Since the molar ratio of sulfur powder to selenium powder in Example 1 is 5:1, the content of Se is lower than that of S. The O element in the material mainly comes from the inevitable oxidation of the material surface.

[0079] The SA-Fe-S / Se-5:1 prepared in Example 1, the SA-Fe-S / Se-1:1 prepared in Example 2, the SA-Fe-S prepared in Comparative Example 1, the SA-Fe-Se prepared in Comparative Example 2, and the SA-Fe-S / Se-1:5 prepared in Comparative Example 3 were ground into powders and used as negative electrode active materials, respectively. The battery performance of the corresponding sodium ion battery negative electrode was measured using CR2032 coin-type battery test materials.

[0080] First, the working electrode was prepared by mixing the SA-Fe-S / Se-5:1 powder prepared in Example 1, a polymer binder (aqueous solution of carboxymethyl cellulose, with a mass fraction of 1.5%) and a conductive material (conductive carbon black) to obtain a slurry, which was coated on a copper foil and dried at 80°C for 12 hours, wherein the mass fractions of the SA-Fe-S / Se-5:1 powder, the polymer binder and the conductive material were 80wt%, 10wt% and 10wt%, respectively. The battery was assembled in a glove box, using a Whatman glass fiber separator and a metal sodium sheet as the counter electrode, and the electrolyte was a diethylene glycol dimethyl ether (DIGLYME) solution of NaPF6, wherein the concentration of NaPF6 was 1M, and the voltage window of 0.01-3V (relative to Na) was 0.01-3V on a LANHE battery test system (CT2001A, Wuhan, China). + / Na) for battery charge / discharge test. Shanghai Chenhua electrochemical workstation CHI660E was used for battery electrochemical impedance test. The test voltage was open circuit voltage and the frequency was 0.01-10 5 Hz.

[0081] The SA-Fe-S / Se-5:1 powder prepared in Example 1 was replaced by SA-Fe-S / Se-1:1 prepared in Example 2, SA-Fe-S prepared in Comparative Example 1, SA-Fe-Se prepared in Comparative Example 2, and SA-Fe-S / Se-1:5 prepared in Comparative Example 3, respectively. The rest of the working electrode preparation and testing process were the same as above.

[0082] Figure 5EIS graphs of sodium ion batteries with SA-Fe-S / Se-5:1 prepared in Example 1, SA-Fe-S / Se-1:1 prepared in Example 2, SA-Fe-S prepared in Comparative Example 1, SA-Fe-Se prepared in Comparative Example 2, and SA-Fe-S / Se-1:5 prepared in Comparative Example 3 as negative electrodes after 10 cycles at a current density of 1A / g. It can be seen from the figure that the prepared materials all show a typical curve graph of a semicircle in the high-frequency region and a straight line in the low-frequency region. Among them, the semicircle diameter of SA-Fe-S / Se-5:1 prepared in Example 1 is the smallest in the high-frequency region, followed by SA-Fe-S / Se-1:1 prepared in Example 2. The semicircle diameters of both in the high-frequency region are smaller than those of Comparative Examples 1-3, indicating that the composite materials prepared in Examples 1 and 2 have faster charge transfer capabilities. The impedance test results show that the SA-Fe-S / Se-5:1 prepared in Example 1 and the SA-Fe-S / Se-1:1 prepared in Example 2 have higher conductivity and faster electron transmission ability, which is mainly derived from the formation of single-phase ternary materials and the wrapping of conductive carbon network. Figure 5 It can also be seen that the slope of the straight line part in the low-frequency region is still higher than that of SA-Fe-S / Se-5:1 prepared in Example 1 and SA-Fe-S / Se-1:1 prepared in Example 2, which is higher than that of Comparative Examples 1-3, indicating that the material has a higher sodium ion diffusion coefficient, can realize rapid sodium ion transport during sodium storage, and is beneficial to the conversion reaction and further improvement of capacity.

[0083] Figure 6 The cycle performance curves of sodium ion batteries with SA-Fe-S / Se-5:1 prepared in Example 1, SA-Fe-S / Se-1:1 prepared in Example 2, SA-Fe-S prepared in Comparative Example 1, SA-Fe-Se prepared in Comparative Example 2, and SA-Fe-S / Se-1:5 prepared in Comparative Example 3 as negative electrodes at a current density of 1 A / g are shown. Figure 6It can be seen that the first charge and discharge specific capacities of the SA-Fe-S / Se-5:1 composite material prepared in Example 1 are 676.92 mAh / g and 847.38 mAh / g, respectively, and the charge and discharge specific capacities can still be maintained at 525.05 mAh / g and 616.46 mAh / g after 676 cycles. The first discharge (charge) specific capacities of the corresponding SA-Fe-S / Se-1:1 prepared in Example 2, SA-Fe-S / Se-1:5 prepared in Comparative Example 3, SA-Fe-S prepared in Comparative Example 1, and SA-Fe-Se materials prepared in Comparative Example 2 are 688.55 mAh / g (480.33 mAh / g), 628.47 mAh / g (539.02 mAh / g), 775.30 mAh / g (512.94 mAh / g), and 698.10 mAh / g (588.10 mAh / g), respectively. In addition, the discharge capacity of SA-Fe-S / Se-1:1 prepared in Example 2 after 678 cycles is 508.22 mAh / g, the discharge capacity of SA-Fe-S prepared in Comparative Example 1 after 700 cycles is 588.10 mAh / g, the discharge capacity of SA-Fe-Se prepared in Comparative Example 2 after 705 cycles is 106.18 mAh / g, and the discharge capacity of SA-Fe-S / Se-1:5 prepared in Comparative Example 3 after 405 cycles is 548.80 mAh / g. The results show that the SA-Fe-S / Se-5:1 composite material prepared in Example 1 using a small amount of selenium source exhibits high sodium storage performance, which is mainly due to the formation of a single-phase ternary FeS 2-x Se x Species can significantly relieve internal stress and improve the electrochemical properties of materials.

[0084] Figure 7 The cycle performance curves of the sodium ion battery with the SA-Fe-S / Se-5:1 prepared in Example 1, the SA-Fe-S prepared in Comparative Example 1 and the SA-Fe-Se prepared in Comparative Example 2 as the negative electrode at a current density of 3A / g. It can be seen from the figure that the discharge specific capacity of the SA-Fe-S / Se-5:1 prepared in Example 1 can reach 225mAh / g after 5231 cycles, which is higher than the SA-Fe-S of Comparative Example 1 (49.91mAh / g after 2042 cycles) and the SA-Fe-Se of Comparative Example 2 (178.66mAh / g after 3000 cycles). The results show that the SA-Fe-S / Se-5:1 composite material prepared in Example 1 has excellent long-cycle performance.

[0085] Figure 8The rate performance of SA-Fe-S / Se-5:1 prepared in Example 1, SA-Fe-S / Se-1:1 prepared in Example 2, SA-Fe-S prepared in Comparative Example 1, SA-Fe-Se prepared in Comparative Example 2, and SA-Fe-S / Se-1:5 prepared in Comparative Example 3 for 10 cycles at different current densities of 0.5 A / g, 1 A / g, 2 A / g, and 5 A / g. Among them, the discharge specific capacities of SA-Fe-S / Se-5:1 prepared in Example 1 at the above-mentioned different current densities are 502 mAh / g, 495.8 mAh / g, 439.46 mAh / g, 444.2 mAh / g, and 352.2 mAh / g, respectively. When the current density returns to 0.5 A / g, the discharge specific capacity can still reach 581.1 mAh / g. When the current density is reduced to 0.1 A / g, the discharge specific capacity can reach 676.9 mAh / g. The discharge specific capacities of SA-Fe-S / Se-5:1 prepared in Example 1 and SA-Fe-S / Se-1:1 prepared in Example 2 at the above different current densities are higher than those of Comparative Examples 1, 2 and 3, indicating that the prepared single-phase ternary iron-based sulfide selenide composite material has a more excellent rate performance. This is mainly due to the unique electronic structure of the single-phase ternary material and the wrapping of the carbon-based material, which can improve the overall conductivity of the material, accelerate the diffusion of electrons at high current density, and reduce the volume expansion caused by the sodium insertion and extraction process at different current densities, thereby maintaining a high sodium storage capacity.

[0086] To further illustrate the excellent electrochemical properties of the iron-based single-phase ternary material prepared by the simultaneous sulfidation and selenization strategy in the sodium ion battery system, the composite material SA-Fe-S-Se was prepared in Comparative Example 4. The composite material adopts the strategy of first sulfidation and then selenization. When used as a negative electrode material for sodium ion batteries, its cycle performance at a current density of 1A / g can be found in Fig. 9 .from Fig. 9 It can be seen that the first cycle charge and discharge specific capacities are 539 mAh / g and 548.5 mAh / g respectively, and the discharge specific capacity after 500 cycles is 493.6 mAh / g. The first cycle charge and discharge specific capacity and the discharge specific capacity after the cycle of the composite material SA-Fe-S-Se are lower than those of Examples 1 and 2. The results show that the single-phase ternary composite material prepared by the simultaneous sulfidation and selenization strategy has better electrochemical properties.

[0087] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a single-phase ternary iron-based sulfide selenide composite material, characterized in that: The specific steps include: (1) A certain amount of sodium alginate is placed in water, and then placed in a water bath, heated and stirred until completely dissolved. After the stirring is completed, the solution is cooled to room temperature, and the gel solution formed after standing to discharge bubbles is solution A, and the mass concentration of sodium alginate in solution A is 0.01-0.05 g / mL; Fe(NO3)3·9H2O is dissolved in water to prepare solution B, and the concentration of Fe(NO3)3·9H2O in solution B is 0.1-0.3 mol / L; (2) adding solution A dropwise into solution B under slow stirring, and a ball-dropping phenomenon occurs. After all solution A is added into solution B, stirring is stopped to obtain a mixture C. The mixture C is placed in a constant temperature water bath for static adsorption. The temperature of the constant temperature water bath is 25 to 50° C., and the static adsorption time is 12 to 36 hours. After the adsorption is completed, the formed spherical substance is washed with deionized water for multiple times. After the washing is completed, the obtained spherical substance is freeze-dried, and the product obtained after the drying is SA-Fe. (3) The SA-Fe powder obtained in step (2) is placed in a porcelain boat A, and the sulfur powder and selenium powder are placed in a porcelain boat B. Specifically, the sulfur powder is placed downstream of the porcelain boat B and the selenium powder is placed upstream of the porcelain boat B. The molar ratio of sulfur powder to selenium powder is 1:1 to 2:

4. The porcelain boat A is placed downstream of a tubular furnace and the porcelain boat B is placed upstream of the tubular furnace. The temperature is then raised to 450 to 700°C in an inert atmosphere at a heating rate of 1 to 4°C / min. The temperature is then maintained at this temperature for a period of time. After the constant temperature is reached, the mixture is naturally cooled to room temperature to obtain a single-phase ternary iron-based sulfur-selenide composite material, which is recorded as SA-Fe-S / Se.

2. The method for preparing the single-phase ternary iron-based sulfide selenide composite material according to claim 1, characterized in that: The water used in step (1) is all deionized water; the heating and stirring temperature is 60-90° C., and the stirring time is 0.5-2 hours.

3. The method for preparing the single-phase ternary iron-based sulfide selenide composite material according to claim 1, characterized in that: The volume of deionized water used for each washing in step (2) is 800 to 1500 mL; the freeze-drying time is 24 to 72 hours.

4. The method for preparing the single-phase ternary iron-based sulfide-selenide composite material according to claim 1, characterized in that: The inert atmosphere in step (3) is N2 atmosphere, and the constant temperature time is 3 to 8 hours.

5. The single-phase ternary iron-based sulfide selenide composite material obtained by the preparation method according to any one of claims 1 to 4.

6. The single-phase ternary iron-based sulfide selenide composite material according to claim 5, characterized in that: The single-phase ternary iron-based sulfide selenide composite material has a mutually cross-linked porous carbon network structure, and the single-phase ternary iron-based sulfide selenide particles are wrapped in the porous carbon network structure.

7. Use of the single-phase ternary iron-based sulfide selenide composite material as claimed in claim 5 as a negative electrode material for sodium ion batteries.

Citation Information

Patent Citations

  • Three-dimensional porous carbon-based selenide / iron sulfide composite material and application thereof in sodium ion battery

    CN117334907A

  • Metal sulfide / carbon composite material and preparation method and application thereof

    CN111146424A

  • FeS<2-x>Sex solid solution cathode material and preparation method thereof

    CN111554874A